Experimental investigation of non-halogenated resin base for carbon fibre reinforced plastics composite - Tan, Serena Chao Hui (Nanyang Technological University, 2021)
Carbon fibre-reinforced plastics (CFRP) are often at risk of fire. Despite having extensive research done on the fire resistance capability of fire retardants (FR) additives that do not produce toxic by-products (ATH and ZB), there is a lack of correlation between the concentration of FR, fire resistance, and their effect on the mechanical properties of CFRP. In an attempt to understand all that, ATH and ZB are incorporated into an epoxy resin and CFRP composites are fabricated using Wet Lay-up. Compression Test is conducted in accordance with ASTM D6641 to identify any ramification due to the addition of additives to the CFRP, while the flammability performance of the composites was analysed using UL94 vertical burning test procedures. Compression strength is the most ideal when the concentration of the additive does not exceed 35% w/w, but an acceptable flammability performance with UL94 V-0 rating requires a minimum combined filler loading of 55% w/w at a 1:1 ratio of ATH and ZB. While C55, C57 and C60 managed to achieve the same flammability performance as a commercial product, the high filler loading also resulted in poor mechanical properties. Thermogravimetric analysis and differential scanning calorimetry analysis results have shown that the resin did not interfere with the curing of the resin, and the lack of fire resistance at lower concentration was due to insufficient additives in the system. The synergistic effect of ATH and ZB can be further studied to create a more optimal resin system for CFRP use.